أثر الرقابة الإدارية على الأداء المالي للوحدات الحكومية: دراسة حالة وزارة المالية والقوى العاملة ولاية النيل الأبيض 2019 م - د الشاذلي عيسى حمد عبد الله; د السماني محمد الغالي نور الدائم (White Nile Journal for Studies and Research, 2020)
The research problem has presented in a form of a main question about the relationship between the managerial controls with the financial performance at government units. The research aims to recognize the managerial system and the range of its effect on the government financial performance, it studied the relationship between managerial control and the irregular cases on the public resources. The research tested the following hypothesis, the managerial control system at the government units has no effect on the financial performance, and the high rates of irregular cases are index of defect in the managerial control system. The financial performance of government does not help the fair application of managerial control system. The research has used the historical, deductive, descriptive analytical research methods. The research has found out a number of findings: the managerial control system at the government has no effect on the financial performance for some factors out that of the control. The internal audit weakness, as a tool of managerial control system, has a relationship with the weakness of academic, practical qualifications. The research recommendations are as fpollow: giving more attention for training of the human resource of the managerial control units, specially the internal audit, and the necessity of effectiveness of the laws that helps the control system and provide the managerial control units with material, technical, and technological requirements.